Kajian Filsafat Hukum Ekonomi Islam terhadap Akad Wakalah: Disharmoni antara al-Muwakkil dan al-Wakil dalam Lembaga Keuangan Syariah - Munandar, Aris; Saefuloh, Irfan; Ardestya Linanjung, Yolanda; Hariyanti, Hariyanti; Apriani, Triana (IAIN Langsa, 2025)
This study aims to deeply analyze the concept and ideal principles of the wakalah contract in Islamic financial institutions. In essence, the wakalah contract is built upon the principles of trust, transparency, and responsibility, where the agent (wakil) acts in accordance with the authority and intent of the principal (muwakkil). However, in practice within Islamic financial institutions, deviations often occur in the implementation of wakalah, such as conflicts of interest and decision-making that does not align with the interests of the clients. This article is a qualitative study employing a normative approach and literature review, which comprehensively examines the legal foundations, sharia principles, and empirical practices of the wakalah contract. The findings indicate that while wakalah has a strong conceptual foundation in Islamic jurisprudence (fiqh muamalah), its implementation in Islamic financial institutions has not yet fully reflected the ideal values of sharia. Strengthening regulatory, ethical, and technical aspects is necessary to ensure that wakalah transactions are conducted fairly and transparently.